Momentum transfer and plasma rotation caused by destabilized eigenmodes in tokamaks. (26th October 2022) - Kolesnichenko, Ya.I.; Kim, Hyun-Tae; Lutsenko, V.V.; Tykhyy, A.V.; White, R.B.; Yakovenko, Yu.V.
Abstract : The influence of magnetohydrodynamic eigenmodes destabilized by energetic ions on the momentum of these ions and concomitant sheared plasma rotation are studied. Two mechanisms affecting rotation are revealed: (i) spatial channelling (SC) – radially separated emission and absorption of the momentum; (ii) mode induced redistribution (MIR) across the magnetic field of the momentum of energetic ions. Forces arising during SC and MIR produce both toroidal and poloidal rotations. In addition, the momentum emission during SC leads to a radial flux of fast ions and generation of a radial electric field. Using the developed theory, estimates were made for the ITER (International Thermonuclear Experimental Reactor) 15 MA baseline scenario. They show that a global toroidicity-induced Alfvén eigenmode destabilized by alpha particles and neutral beam injection can result in significant radial electric field and forces applied to plasma. However, available data are not sufficient for a reliable prediction of the effects of SC and MIR in ITER. In general, one can expect that sheared rotation arising after destabilization of Alfvén modes and fast magnetoacoustic modes by energetic ions will tend to suppress the turbulence and improve plasma performance. The importance of plasma rotation is supported, in particular, by the fact that during the JET DTE1 experimental campaign the best parameters were achieved in a deuterium–tritium discharge where the rotation frequency was largest.